Evaluation of Root-End Resections Performed by Er, Cr: YSGG Laser with and without Placement of a Root-End Filling Material - John Sullivan; Roberta Pileggi; Claudio Varella (International Journal of Dentistry)
Microleakage following root-end resections has a direct influence on the outcome of surgical endodontic procedures. This study compared the microleakage after root-end resections performed by the Er, Cr: YSGG laser or carbide burs with or without the placement of MTA, and evaluated the presence of microcracks and gaps at the interface of GP/MTA and the canal walls. Ninety single-rooted teeth were instrumented, obturated with GP and AH-Plus sealer, and divided into 3 experimental groups: (I) root-end resections were performed with the laser and G6 tips (parameters: 4.5 w, 30 pps, 20% water and 50% air); (II) Lindeman burs were used, without the placement of MTA; (III) the burs were used followed by root-end fillings with MTA, and one control (IV) of five unobturated roots resected with the burs. The samples were prepared for microleakage (𝑛=20) and SEM (𝑛=10) analysis. They were immersed in 1% methylene blue, decalcified, cleared, and evaluated for dye penetration (mm2) with the ImageJ software. Epoxy-resin replicas of the root-ends were analyzed by SEM for gaps (𝜇m2) and microcracks. Microleakage results were 0.518±1.059, 0.172±0.223, and 0.158±0.253, for the laser (I), no root-end filling (II), and MTA (III) samples, respectively, (ANOVA 𝑃=.02). The laser (7831.7±2329.2) and no root-end filling (7137.3±1400.7) samples presented gaps. Whereas, none was found in the MTA (ANOVA 𝑃=.002). Microcracks were not observed. The MTA group demonstrated statistically less leakage and better adaptation to the canal walls when compared to the other groups. There was no correlation between the size of the gaps and the degree of microleakage.